2021
DOI: 10.1088/2631-8695/ac2e10
|View full text |Cite
|
Sign up to set email alerts
|

Turning of steels under various cooling and lubrication techniques: a review of literature, sustainability aspects, and future scope

Abstract: In this review work, various conventional cutting fluids and their application methods have been discussed, which serve different functions such as cooling, lubrication, cleaning, and corrosion protection during the machining process. According to the available research, issues associated with the conventional ones have beenidentified concerning sustainability metrics, i.e., economic, environmental, and social dimensions. These issues necessitated shifting toward sustainable alternatives. All such alternatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 228 publications
0
7
0
Order By: Relevance
“…The influence of S s and C fr is shown in Figure 14. Runs (8,13), (18,28), and (23,26) clearly show the effect of C fr . In the afore mentioned experimental runs, it was found that coolant behaviour varied according to how many other parameters were combined.…”
Section: Parameter Interaction Effectsmentioning
confidence: 92%
See 1 more Smart Citation
“…The influence of S s and C fr is shown in Figure 14. Runs (8,13), (18,28), and (23,26) clearly show the effect of C fr . In the afore mentioned experimental runs, it was found that coolant behaviour varied according to how many other parameters were combined.…”
Section: Parameter Interaction Effectsmentioning
confidence: 92%
“…A detailed review [23] was carried out on cutting fluids and their methods of application during various machining operations. The review also consolidated issues associated with conventional and concerned sustainability metrics.…”
Section: Introductionmentioning
confidence: 99%
“…The MQL, a sustainable solution, introduces bio-lubricants at minimal flow rates into the tool/workpiece interface using high-pressure airflow. MQL has garnered attention for its cost-effectiveness, environmental benefits, and enhanced safety [13,14]. Research demonstrates its ability to improve surface quality, reduce tool wear, and extend tool life in various machining processes, such as turning, milling, and grinding, across diverse materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to use lubricating oils for the lower wear and longer service life of steel since lubricating oils can effectively reduce the friction and wear of rubbing surfaces [18,19]. Therefore, comprehensive understanding of the tribological behaviour of DeepCryoTreat-EN24 steel under lubrication condition is also important to be successfully applied in mechanical components.…”
Section: Introductionmentioning
confidence: 99%